A risk management framework for distributed agile projects - Shrivastava, Suprika Vasudeva; Rathod, Urvashi (Information and software technology, 2017)
Distributed agile development (DAD) approach has been adopted by the software companies for cost and time benefits. However, it causes significant challenges considering the contradicting nature of the agile and distributed development. The objective of this study is to develop a risk management framework that comprises the perceived risks in DAD projects, their causes and the methods used in industry for managing those risks. This work is an extension of an exploratory study, wherein, DAD practitioners reported the risks they face in projects and the methods they use for managing those risks. The identified risks were further categorized based on their relevance to different aspects of DAD projects. In this extension, industry practitioners ranked the risks for their impact on DAD projects and rated the methods for the frequency of their use in projects. As the number of risks under each category was large for ranking, they were grouped under the risk areas within each category. The ranking of risk categories, risk areas and risk factors for their impact on DAD projects manifests their importance. The framework includes ranked risks, their causes and the risk management approaches. It was partially implemented in live projects in three different companies and was found to be beneficial. The perceived impact of the risk categories, ‘Group Awareness’, ‘External Stakeholder Collaboration’ and ‘Software Development Life Cycle’ on DAD projects has been found to be high and caused by the properties of Distributed Software Development (DSD). The partial validation of the framework in three companies reported the elimination of majority of risk factors and/or reduction in their impact. DAD projects provide significant benefits but hold substantial risks due to the contradiction between distributed development and agile practices. The reported framework could effectively minimize the DAD risks in practice.